Pharmacokinetic bioequivalence of the fixed-dose combination of pertuzumab and trastuzumab administered subcutaneously using a handheld syringe or an on-body delivery system - Chris Wynne; Bei Wang; Rong Deng; Junyi Li; Daniel Eiger; Fabiola Bene Tchaleu; Sarah Heeson; Eleonora Restuccia (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose This randomized, open-label, two-arm, parallel-group, single dose, multi-center phase I study (ClinicalTrials.gov ID, NCT05275010) investigated the comparability of the pharmacokinetics of a new formulation combining pertuzumab (P) and trastuzumab (H) in one fixed-dose combination for subcutaneous injection (FDC SC) using a proprietary on-body injector (OBI) or a handheld syringe with hypodermic needle in healthy male subjects. Methods Healthy male subjects were randomized 1:1 to either PH FDC SC using a handheld syringe (Arm 1) or an OBI device (Arm 2). Co-primary endpoints were: (i) area under the time–concentration curve (AUC) from the start of dosing to day 63 (AUC0–62) of serum P, (ii) maximum serum concentration (Cmax) from start of dosing to 63 days of serum P, (iii) AUC from the start of dosing to day 63 (AUC0–62) of serum H, and (iv) Cmax from start of dosing to 63 days of serum H. Safety was a key secondary endpoint. Liquid chromatography coupled to tandem mass spectrometry was used to measure pertuzumab and trastuzumab simultaneously in serum samples. Results The obtained geometric mean ratios for Cmax and AUC0–62 were within the pre-specified bioequivalence margins (0.80, 1.25) for both P and H, therefore meeting the criteria for bioequivalence. No discontinuations due to safety reasons were reported. Overall, the final safety analysis with longer follow-up was consistent with the primary analysis; there were no new or unexpected safety findings. Conclusion This study demonstrated the feasibility of a hands-free device approach to deliver pertuzumab and trastuzumab in one fixed-dose combination for subcutaneous injection without compromising pharmacokinetics and safety.